Numerical evaluation of conformal mapping and its inverse for unbounded multiply connected regions - Yunus A.A.M.; Murid A.H.M.; Nasser M.M.S. (2024)
A boundary integral equation method for numerical evaluation of the conformal mapping and its inverse from unbounded multiply connected regions onto five canonical slit regions is presented in this paper. This method is based on a uniquely solvable boundary integral equation with the adjoint generalized Neumann kernel. This method is accurate and reliable. Some numerical examples are presented to illustrate the effectiveness of this method.